Barriers influencing task-shifting for the management of depression in people living with HIV: a study from West Africa IeDEA cohort collaboration. Issue 3 (4th March 2021) - Bernard, Charlotte; Seydi, Moussa; Tanon, Aristophane; Messou, Eugène; Minga, Albert; Font, Hélène; Dabis, François; ,
ABSTRACT: Depression is highly prevalent in people living with HIV (PLHIV) worldwide. As mental health specialists are scarce in sub-Saharan Africa (SSA), the World Health Organization (WHO) encourages task-shifting. We aimed to evaluate the barriers that could compromise task-shifting in front-line health care workers (HCWs) who provide HIV integrated care in West Africa. We collected knowledge, attitudes and practices (KAP) information on symptoms, causes and management of depression in PLHIV in care in four clinics in Senegal and Côte d'Ivoire (N = 168). The main barriers that could compromise task-shifting came from poor knowledge, particularly on symptoms and causes. Knowledge was more limited in HCWs other than medical doctors (good answers < 70%). The access to a depression training was limited (32.7%) and was the main factor associated to poor knowledge on depression. Even when social distance and barriers to practice were low (70.8% and 69.6%, respectively), some barriers persisted. More than half of respondents considered that diagnosis and management needed to be performed by a specialist. To guarantee the success of task-shifting, in the perspective of integrated care, efforts are needed to improve the access to specific training on depression considering screening, management, but also perceptions and attitudes, as some barriers subsist.